(untitled) (International Journal of Biomedical and Advance Research, 2015)
Seminoma is the most common single histologic type of germinal testicular neoplasms. The undescended testicles carry 20-48 times higher potential for malignant transformation. We present a 30 year old male with malignant undescended intra abdominal testis.